2016
DOI: 10.1021/acs.est.6b01062
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Environmental Exposure to Microcystin and Aflatoxin as a Risk for Renal Function Based on 5493 Rural People in Southwest China

Abstract: Although the nephrotoxicity of microcystin and aflatoxin has been observed in animal and clinical cases, few population data are available. We conducted a cross-sectional study in Southwest China to investigate the association of renal function indicators (RFIs, including BUN, SCr, and eGFR) with exposure to microcystin and aflatoxin in 5493 members of the general population. Microcystin-LR levels in water and aquatic products and aflatoxin B1 levels in daily foods were measured by ELISA, and individual estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
49
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 78 publications
(52 citation statements)
references
References 58 publications
3
49
0
Order By: Relevance
“…For these indicators, years in college was divided into junior (years 1–2) or senior (years 3–4), a smoker was defined as someone who had smoked at least one cigarette per day for more than six months or quitting less than six months prior to recruitment [25]; a drinker was defined as someone who drinks alcohol at least once a week for more than six months [25]. …”
Section: Methodsmentioning
confidence: 99%
“…For these indicators, years in college was divided into junior (years 1–2) or senior (years 3–4), a smoker was defined as someone who had smoked at least one cigarette per day for more than six months or quitting less than six months prior to recruitment [25]; a drinker was defined as someone who drinks alcohol at least once a week for more than six months [25]. …”
Section: Methodsmentioning
confidence: 99%
“…Briefly, from June to July in 2013, 6467 people aged from 30 to 85 years old and having lived in Lidu and Yihe for at least 10 years were recruited in the study. Among them, 5493 individuals (2067 men and 3426 woman) who completed the questionnaires and clinical examinations were included in the study 20 .…”
Section: Methodsmentioning
confidence: 99%
“…The assessment of microcystin and aflatoxin exposure was performed according to the methods previously described 20, 44 . Briefly, 5 L of eight types of source water and drinking water, and five types of carp were collected once a month for microcystin-LR analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MC-LR influences the structure and function of the liver, kidney, brain, testicle, and thyroid gland in animals [2][3][4][5][6]. In addition, we have previously reported that MC-LR impaired liver and kidney function in humans [7,8].…”
mentioning
confidence: 99%